1999
DOI: 10.1159/000017187
|View full text |Cite
|
Sign up to set email alerts
|

<i>Tau</i> Immunoreactivity Detected in Human Plasma, But No Obvious Increase in Dementia

Abstract: Tau proteins are central to the neuropathology of Alzheimer’s disease and tau levels in cerebrospinal fluid are elevated in affected individuals. In this study, we investigated the presence of tau in plasma from subjects with Alzheimer’s disease (n = 16), frontotemporal dementia (n = 10), vascular dementia (n = 16) and from healthy controls (n = 15). By using an ELISA with monoclonal tau antibodies, tau immunoreactivity was detected in approximately 20% of the subjects. However, no difference between the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…It is possible that tau entering serum compartments is enzymatically cleaved, loses its C-terminal part, and consequently the first step of t-tau assay becomes unfeasible even though p-tau is still efficiently detected. On the other hand, in a previously published study [31], serum tau immunoreactivity detection in patients with dementia was approximately 20% (similar to our results) but after gel filtration peak reactivity was found in the 160kD fraction. This indicated an unexpected high molecular weight, and suggested the existence of tau-like molecules or polymers of lowmolecular weight tau.…”
Section: Figure 1 Linear Regression Line With 95% CI Band For Csf Tasupporting
confidence: 92%
“…It is possible that tau entering serum compartments is enzymatically cleaved, loses its C-terminal part, and consequently the first step of t-tau assay becomes unfeasible even though p-tau is still efficiently detected. On the other hand, in a previously published study [31], serum tau immunoreactivity detection in patients with dementia was approximately 20% (similar to our results) but after gel filtration peak reactivity was found in the 160kD fraction. This indicated an unexpected high molecular weight, and suggested the existence of tau-like molecules or polymers of lowmolecular weight tau.…”
Section: Figure 1 Linear Regression Line With 95% CI Band For Csf Tasupporting
confidence: 92%
“…They are generally expensive to perform routinely and lumbar puncture is invasive and often unpleasant. Moreover a large variability exists in the literature as to CSF biomarker diagnostic accuracies and cut-offs, hampering or delaying their everyday application in the clinical setting [29, 30] and their potential use as indicators of prodromal AD.…”
Section: Biomarkersmentioning
confidence: 99%
“…The interassay variation is between 1.7 and 6% [13]. The probe volume was increased to 75 µl and the conjugate decreased to 25 µl to lower the detection limit for serum samples [10]. …”
Section: Methodsmentioning
confidence: 99%
“…So far, there is limited experience with serum levels of tau protein. In one study, no differences of plasma tau protein levels were found between patients with dementia and controls [10]. …”
Section: Introductionmentioning
confidence: 99%